2022
DOI: 10.1038/s41598-022-25368-y
|View full text |Cite
|
Sign up to set email alerts
|

Cofactors, age at onset, allergic comorbidities and gender are different in patients sensitized to omega-5 gliadin and Pru p 3

Abstract: Aim of this study is to clarify the impact of cofactors on allergic reactions in patients sensitized to LTP and ω-5-gliadin. We retrospectively examined the charts of our outpatients from January 2015 to July 2019 and identified 157 patients seen for urticaria/angioedema or anaphylaxis after a meal, in presence or absence of cofactors and sensitized to LTPs (Pru p 3 and/or Tri a 14) and/or ω-5-gliadin (Tri a 19). we compared LTPs-positive patients and those sensitized to Tri a 19 in order to assess the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Some of these observations confirm the results reported in an Italian study that assessed the effect also of other co-factors in patients sensitized to Pru p 3 and Tri a 14, confirming a later onset of the co-factors related reactions in adulthood rather than childhood. Also in this case, in fact, exercise was the most common co-factor reported (31.9%), followed by humid-heat in 31.2%, pollen peak in 17.8%, NSAIDs in 15.9%, alcohol in 9.6%, and PPI (pump proton inhibitors) in 4.5% ( 50 ).…”
Section: The Role Of the Co-factors In Allergic Reactions To Nsltpsmentioning
confidence: 78%
See 1 more Smart Citation
“…Some of these observations confirm the results reported in an Italian study that assessed the effect also of other co-factors in patients sensitized to Pru p 3 and Tri a 14, confirming a later onset of the co-factors related reactions in adulthood rather than childhood. Also in this case, in fact, exercise was the most common co-factor reported (31.9%), followed by humid-heat in 31.2%, pollen peak in 17.8%, NSAIDs in 15.9%, alcohol in 9.6%, and PPI (pump proton inhibitors) in 4.5% ( 50 ).…”
Section: The Role Of the Co-factors In Allergic Reactions To Nsltpsmentioning
confidence: 78%
“…Furthermore, it is worth recalling that NSAIDs intake to control menstrual pain, as well as during acute infections, is a frequent practice, determining the risky concomitance of multiple co-factors ( 50 ).…”
Section: The Role Of the Co-factors In Allergic Reactions To Nsltpsmentioning
confidence: 99%
“…10 Complement activation by immune complexes can result in release of complement 3a, complement 4a, and complement 5a anaphylatoxins that can cause histamine release via an IgE independent mechanism. 11 It was shown that degranulation of mast cells via anaphylatoxins is restricted to certain subpopulations of mast cells because mucosal mast cells do not express anaphylatoxin receptors. 12 Reciprocal interactions between sensory nerves and mast cells happen via vasoactive intestinal peptides and neuropeptides (substance P), leading to stimulation and degranulation of mast cells potentiation of pruritus and inflammatory response.…”
Section: Mast Cell Interactions With Nervous Systemmentioning
confidence: 99%
“…10 Complement activation by immune complexes can result in release of complement 3a, complement 4a, and complement 5a anaphylatoxins that can cause histamine release via an IgE independent mechanism. 11 It was shown that degranulation of mast cells via anaphylatoxins is restricted to certain subpopulations of mast cells because mucosal mast cells do not express anaphylatoxin receptors. 12 Reciprocal interactions between sensory nerves and mast cells happen via vasoactive intestinal peptides and neuropeptides (substance P), leading to stimulation and degranulation of mast cells potentiation of pruritus and inflammatory response.…”
Section: Mast Cell Interactions With Nervous Systemmentioning
confidence: 99%